Assessment of behavioural effects following treatment with haruan traditional formulation in brain-damage induced Sprague dawley rats - Mohd Shafri, Mohd Affendi; Mohamed, Farahidah; Md. Jaffri, Juliana; Ithnin, Hairuszah; Kyu, Kim Min; Mat Jais, Abdul Manan (2013)
Neurodegenerative conditions continue to affect a large number of people. Despite numerous studies carried out in the last few decades, no effective treatment has been found and current management of neurodegenerative conditions are not effective, marred by side-effects, costly and could only provide symptomatic alleviations. Haruan or Channa striatus, is rich in many important amino acids and fatty acids, which may act as suitable pharmacological modulators to neuron cells as they have potential to cross the blood-brain barrier, have anti-oxidative action and may trigger neurite growth receptor on neuron cell’s surface. In an in vivo experiment using Sprague Dawley rats, the effect of haruan traditional formulation (HTF) on rats’ nose-dipping and rearing behaviours in neuroprotective and neuroregenerative assays was studied using a hole board maze. Two neurodegenerative agents, ketamine and methamphetamine, were given intraperitoneally, 4 four times a day at 2 hour interval at different doses and rats were further classified into a short (1 day) or long exposure (5 days) groups (n=5 per group). It was found that HTF could provide some neuroprotective (p < 0.01 for the nose dip and p < 0.05 for rearing; one way ANOVA with Tukey’s post hoc analysis) and neuroregenerative (p < 0.001 for both nose dip and rearing; one way ANOVA with Tukey’s post hoc analysis) effects on rats’ behaviour for the long exposure to ketamine group and not in other groups. The results suggests that HTF is studied further for its potential neuro-modifying properties, and treatment of neurodegenerative condition must take into account type and nature of degeneration as well as functional and numerical changes of the brain.